MuleSoft Platform architect's guide a practical guide to using Anypoint Platform's capabilities to architect, deliver, and operate APIs - Bafna, Jitendra; Andrews, Jim (Packt Publishing Limited, 2024)
Unlock the power of Anypoint Platform by leveraging MuleSoft methodology, Accelerators, runtime engines, and management tools to deliver secure, high-value APIs and integration solutions across the enterprise Key FeaturesDiscover Anypoint Platform's capabilities for creating high-availability, high-performance APIsLearn about AnyPoint architecture and platform attributes for Mule app deploymentExplore best practices, tips, and tricks that will help you tackle challenging exam topics and achieve MuleSoft certificationPurchase of the print or Kindle book includes a free PDF eBookBook Description We' re living in the era of digital transformation, where organizations rely on APIs to enable innovation within the business and IT teams are asked to continue doing more with less. As such, this book will help you deliver a robust, secure, and flexible enterprise API platform, supporting any required business outcome.
Keywords: COMPUTERS / Software Development & Engineering / Tools